Study of Magnesium Level as an Indicator of Diabetic Complications - Kumar Nawal, Subodh; Srivastava, Chandrashekhar (International Journal of Medical Research and Review, 2015)
Background: Type 2 diabetes has become a leading cause of morbidity and mortality world over. Magnesium depletion has a negative impact on glucose homeostasis and insulin sensitivity in patients with Type 2 diabetes. Magnesium deficiency can lead to development of complications such as retinopathy, nphropathy, thrombosis and hypertension. Material and Methods: The case control type of study was carried out on 50 age and sex matched healthy controls and 50 type 2 diabetic patients who attended the outpatient and inpatient department of medicine in tertiary care medical institute. All patients and controls underwent thorough clinical examination and estimation of serum magnesium, FBS, PPBS, lipid profile and urea, creatinine levels. Results: 46% of diabetic patients had low serum magnesium levels (Mg2+ level<1.5mg/dL) and 6% of controls had low serum magnesium levels (Mg2+ level<1.5mg/dL). The mean serum magnesium levels were 1.79±0.34mg/dL and 2.12±0.29mg/dL, in diabetics and controls respectively (p value < 0.0001 highly significant). In this study hypomagnesaemia (Mg2+ level < 1.5mg/dl) was correlating with neuropathy and retinopathy, and the results were highly significant. Conclusion: This study demonstrated that Low Magnesium status is common in Type 2 diabetes mellitus patients when compared to non diabetic controls. It may be prudent in clinical practice to periodically monitor plasma magnesium concentration in diabetic patients. If plasma magnesium is low, an intervention to increase dietary intake of magnesium maybe beneficial.